New Trends In Islamic Education: The Rise Of Servant Leadership In Pesantren - Huzali, Ikhsan; Aimah, Siti; El Fayoumi, Ziyad (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
This study explores the emergence of servant leadership as a transformative model in the context of Islamic educational leadership at the Darussalam Blokagung Islamic Boarding School. Guided by Greenleaf's servant leadership theory and integrated with Islamic leadership values ​​(khidmah, amanah, and ukhuwah), this study analyzes how traditional authoritative leadership has evolved into a participatory and human-centered model that aligns with the moral and spiritual ethos of the Islamic boarding school. Using a qualitative case study approach, data were collected through in-depth interviews with seven key informants (including kiai, teachers, and students), participant observation, and document analysis over a six-month period. Data were analyzed using thematic analysis to identify patterns of change and meaning construction, while triangulation ensured contextual validity and depth. The findings reveal three main themes: (1) Transformation of leadership style from an authoritarian model to servant leadership; (2) Internalization of Service Values ​​in Student Development; and (3 Changes in the Organizational Culture of Islamic Boarding Schools to be More Inclusive and Participatory. This transformation not only enriches the theory of servant leadership in Islamic education, but also offers practical insights for educational leaders and policy makers in designing leadership training and institutional reforms that are responsive to contemporary challenges.